2010
DOI: 10.1002/pen.21769
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear melt rheology and extrudate swell of acrylonitrile‐butadiene‐styrene and organoclay‐filled acrylonitrile‐butadiene‐styrene nanocomposite

Abstract: Melt viscoelastic behavior and the die swell of Acrylonitrile‐Butadiene‐Styrene (ABS) and ABS/clay nanocomposites varying in organoclay loading were studied. A pronounced low‐frequency nonterminal behavior exhibited in linear viscoelastic experiments along with an apparent yield stress in transient startup flow tests suggested the existence of a network type, because of interconnection of rubber particles in ABS matrix. From the results of linear and nonlinear viscoelastic measurements, it was found that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
8
0
4
Order By: Relevance
“…that all the nanocomposite samples exhibited the MWCNTs induced solid‐like response at low frequencies, but the response in the case of PS was by far stronger. This suggests that the MWCNTs have a much greater affinity toward PS compared with that toward PP and PMMA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…that all the nanocomposite samples exhibited the MWCNTs induced solid‐like response at low frequencies, but the response in the case of PS was by far stronger. This suggests that the MWCNTs have a much greater affinity toward PS compared with that toward PP and PMMA .…”
Section: Resultsmentioning
confidence: 99%
“…The properties of these polymers are summarized in Table . Considering the importance of kinetic parameters in determination of MWCNT's localization, the apparent viscosity corresponding to the shear rate in the internal mixer and zero shear viscosity were estimated at 60 and 0.05 s −1 , respectively (Table ) . The carbon nanotubes used in this study were commercially available as MWCNTs, NC‐7000, from Nanocyl, Belgium.…”
Section: Methodsmentioning
confidence: 99%
“…It can be clearly seen that the nanocomposite samples exhibit a strong solid‐like behavior and viscosity upturn at a low‐frequency range whose extent increases with MWCNTs content. This behavior is known to be an indication of three‐dimensional physical networks formed between particle–particle and/or particle–matrix, whose extent is determined by degree of dispersion and concentration of MWCNTs . The results imply that the MWCNTs are in the PMMA matrix as well as the other two blend components.…”
Section: Resultsmentioning
confidence: 99%
“…Extrudate swell, also called die swell, is one of the most important viscoelastic responses of polymer melts and play a key role in processability of polymers and die design in extrusion process. According to Saadat et al, 2010 the presence of organoclay reduced die swell of ABS/clay nanocomposites and this was explained in terms of great surface area and anisometric nature of organoclay tactoids and/or platelets, which promote energy consumption and less energy to be stored in chains. The OMMT/ABS nanocomposite materials were subjected to a series of five succesive extrusion cycles, in a co-rotating twin screw extruder and the effect of reprocessing on the properties of this compound was investigated by Karahaliou & Tarantili, 2010.…”
Section: Characterization Of Abs/organoclay Nanocompositesmentioning
confidence: 99%
“…Furthermore, nanocomposites prepared by the SOAM method showed more solid-like behaviour and exhibited higher increase of storage modulus throughout the frequency range, than those prepared by solution blending. From the results of linear and nonlinear viscoelastic measurements in ABS/clay melts it was found that, in addition to the physical network originated from interconnection of rubber particles, a 3D network is formed between organoclay platelets and/or tactoids that causes reduced temperature dependence of linear viscoelastic properties of nanocomposite samples as compared with ABS matrix (Saadat et al, 2010). Extrudate swell, also called die swell, is one of the most important viscoelastic responses of polymer melts and play a key role in processability of polymers and die design in extrusion process.…”
mentioning
confidence: 99%